Implementasi IoT dengan ESP 32 Untuk Pemantauan Kondisi Suhu Secara Jarak Jauh Menggunakan MQTT Pada AWS - Austin, Calvin; Mulyadi, Melisa; Octaviani, Sandra (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2022)
The development of the internet of things (IoT) creates many new innovations in the industrial sector aimed at increasing effectiveness. One of them is to monitor the condition of industrial process machines remotely as discussed in this study. This monitoring can be done using a device connected to the internet. The design of this system requires a microcontroller with an ESP32 wifi module as a data receiver and sender. The data sent is data from the temperature sensor. The data is in the form of simulation data generated from the program and has a random number. Machine-to- server data communication uses the Message Queuing Telemetry Transport (MQTT) protocol. The entire machine-to-server, server-to-server communication system will be carried out in the cloud using a cloud computing platform, namely Amazon Web Services (AWS). The test results show that the payload and temperature data sent from the microcontroller can be stored in the database. To see the reliability of the system, two Normal and Stress Tests were carried out, with a success percentage of 100% fo r data storage to the database on two tests and 16.67% failure in sending data on the Stress Test. The two tests were arranged under different conditions.